The Role of Education in Increasing Social Awareness and Community Participation: A Case Study in Teluk Bintuni, West Papua - Alim Jaizul; Dhika Surya (International Journal of Business, Economics, and Social Development, 2025)
This study examines the role of education in increasing social awareness and community participation in Teluk Bintuni, West Papua, an area rich in natural resources but still lagging behind in terms of education and welfare. Using a qualitative approach with a case study method, this study explores in depth how education contributes to social change and the factors that influence its effectiveness. Data collection was conducted through in-depth interviews, participant observation, document analysis, and Focus Group Discussions (FGD) involving local communities, educators, community leaders, local governments, and civil society organizations. The results of the study showed a positive correlation between education levels and levels of social awareness and community participation in development. Statistical data shows that the community's education profile is still low with 18.4% not attending school, 35.6% having elementary school education, 25.3% having junior high school education, 15.2% having high school education, and only 5.5% having higher education. The study identified four main inhibiting factors: limited access to education, lack of qualified educators, low community awareness of the importance of education, and local cultural aspects that limit educational participation. To address these challenges, five strategies are recommended: improving educational infrastructure, training educators, developing non-formal education programs, utilizing technology, and collaborating with civil society organizations and the private sector. This study makes an important contribution to understanding the linkages between education, social awareness, and community participation in remote areas, and provides practical recommendations for developing more effective and sustainable education policies.